Versatility of ARD1/NAA10-mediated protein lysine acetylation - Tam Thuy Lu Vo; Chul-Ho Jeong; Sooyeun Lee; Kyu-Won Kim; Eunyoung Ha; Ji Hae Seo (Experimental and Molecular Medicine, 2018)
Protein modification: Effect on activity Enzymes that modify proteins by adding an acetyl group have profound effects on metabolism and development, as well as disease. This process, known as acetylation, is carried out by KAT proteins, which are present throughout the body. Although acetyl groups are small, acetylation can change a protein’s electrical charge and shape, and even alter its function. Ji Hae Seo at Keimyung University School of Medicine in Daegu, South Korea, and co-workers reviewed the roles of KAT proteins in health and disease. They report that KAT proteins control gene expression, switch metabolic pathways on or off, and regulate development. Malfunction can lead to various disorders, including neurodegeneration and tumor growth. The researchers highlight several KAT proteins, in particular an enzyme that acetylates the amino acid lysine, that are promising targets for treatment of diseases, including cancer.